Vulnerabilidade socioambiental de áreas urbanizadas no entorno de bacias hidrográficas em Belém - Pará - SADECK, Carla Cristina de Azevedo (Universidade Federal do Pará, 2019)
The purpose of de thesis is to analyse the social eviromment vulnerability of urbanized áreas wich surround watersheds, also preventive managenent measures linked to it. To this end two areas have been studied: Curió-Utinga and Cremação wich currently suffer from constant overflows. Intervieus were done with these areas residents to collect data wich have been tabulated and analyzed by tracing their social economic profile. Besides this the research a need to identify management projects being implemented by the civil defense and management agencies in charge. As a resultit was checked that Curió-Utinga doesn’t have a defined management project that cases about the social economic profile of it’s residents. Counting only wich isolated measurements made by the Civil Defense to alert and prevent flooding episodes. Cremação area belong to PRONABEM project and one of the projects objective is to decrease the overflows in the area and implementation of basic sanitation. Despite the fact that here is no urbanization project that takes the social economic profile of the residents into account the performed seems to be the beginning of public management in action to reduce the impacts caused by the rain.